Pension Strategies of Workers in a Country Getting Old before Getting Rich - Sonia Buchholtz; Jan Gaska; Marek Góra (Institute of Labor Economics (IZA), 2018)
The downward trend in replacement rate is going to affect the material wellbeing of Polish future retirees. The aim of this paper is to identify the pension strategies working Poles undertake to counteract future deterioration in material conditions, with particular interest in saving practices and labour market activity. We make use of the Pension awareness of Poles survey data (N=1006) and apply quantitative methods: binary logistic regressions and principal component analysis (PCA). We distinguish between first-best and second-best strategies. The former relates to accumulating pension wealth, while the latter to the range of actions aimed at making ends meet, provided insufficient benefit. The results show that there is a poor relationship between knowledge, plans and behaviour. Moreover, knowledge itself is limited. Even though the awareness of the worsening conditions of retirees-to-be is increasing, little is being done to counteract it. Among various demographic and socio-economic descriptors income and education play an important role in distinguishing patterns, as well as status of self-employed. Three second-best strategies have been distinguished: own responsibility, external support, rebellion. We conclude that information policy on the pension system should be improved, and the incentives for older workers to continue their careers should be strengthened.
Keywords: J26; D14; D91; 330; pension system; population ageing; supplementary saving; labour force